Gestión de los procesos de adquisición de bienes y servicios en el cuerpo de bomberos - Abril Campuzano, Elizabeth María (2020)
This case study has as its subject MANAGEMENT OF THE PROCESSES OF ACQUISITION OF GOODS AND SERVICES IN THE FIRE DEPARTMENT, the same that was developed in the Fire Department of the city of Babahoyo, is a public institution attached to the Municipality of the canton, the issue arises as a consequence of the mismanagement of public companies in the process of acquiring goods and services that are of vital importance for satisfying the needs of citizens in general. The applicable legal regulations of public contracting in Ecuador were analyzed, the application of essential plans for the fulfillment of strategic objectives in public sector entities, and the existing problems that contribute to processes being delayed in the institution under study. The correct application of the Annual Recruitment Plan in the Fire Department of the City of Babahoyo is proposed, as well as the achievement of the planning phases so that the contracts are carried out according to certain programs where the institution is located. paid for these essential goods and services for its workers and the population.